Waqaf Produktif dan Kesejahteraan Masyarakat: Melalui Transformasi Ekonomi Melalui Waqaf Produktif: Productive Waqf and Community Welfare: Through Economic Transformation Through Productive Waqf - Enceng, Enceng Iip Syaripudin; Gini Gaussian; Rani Surya Resiana; Deni Konkon Furkony; Rano Nurhada (Program Studi Ekonomi Syariah, 2024)
Productive waqf is the main choice when people are in a slump of acute poverty. With productive waqf, it means that the existing waqf gets the main priority aimed at more productive efforts. Productive waqf is a medium to create economic justice and welfare, reduce poverty, develop social security systems, provide health care facilities, and develop education. This phenomenon makes the discussion of waqf productive, especially if it is associated with improving the economic welfare of the community which is very important to do. In this study, a qualitative research method with a phenomenological approach is used. Meanwhile, the study method used is a method in the form of an analytical explanatory descriptive study. With this approach, the researcher tries to understand the model of productive waqf empowerment in Indonesia, in empowering the economic welfare of the community. The models that will be studied from the empowerment of productive waqf in Indonesia are: the model of productive waqf empowerment in the management of investing Waqf Assets, Waqf investment has great potential to be developed in Indonesia. Because with this waqf model, the mobilization reach will be much more evenly distributed to community members compared to the traditional-conventional waqf model, namely in the form of physical property that is usually carried out by relatively capable families. Keywords: Waqaf,; Welfare; Community; Economic Transformation;